2020
DOI: 10.1021/acsami.0c08297
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Surface Oxygen Groups on the Electrochemical Behavior of Porous Carbons as Anodes for Lithium-Ion Batteries

Abstract: The present study elucidates the role of surface oxygen functional groups on the electrochemical behavior of porous carbons when used as anodes for Li-ion batteries. To achieve this objective, a carbon xerogel (CX) obtained by pyrolysis of a resorcinol-formaldehyde gel was modified by different post-synthesis treatments in order to modulate its surface chemistry while maintaining its external surface constant. Various surface modifications were obtained by oxidation in air, insitu polymerization of dopamine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Our results agree well with previously reported data that the increased concentration of nitrogen, mainly pyridinic form, is one of the reasons for improving Na-ion storage capacity [14,15,18]. Piedboeuf et al found that among the oxygen-containing functionalities only carbonyl groups resulted in the increased storage capacity of Li + ions [93]. That also is in accordance with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Our results agree well with previously reported data that the increased concentration of nitrogen, mainly pyridinic form, is one of the reasons for improving Na-ion storage capacity [14,15,18]. Piedboeuf et al found that among the oxygen-containing functionalities only carbonyl groups resulted in the increased storage capacity of Li + ions [93]. That also is in accordance with our results.…”
Section: Discussionsupporting
confidence: 94%
“…C-O=C at a binding energy of 530.5 eV corresponded to the high number of defect sites containing low oxygen coordination [20]. O=C at a binding energy of 531.7 eV could be ascribed to the multiplicity of physisorbed water at and within the surface [17,21]. The results of XPS demonstrated a mixed valence containing Co 2+ , Co 3+ , Ni 2+ and Ni 3+ , which was consistent with previous reports [22].…”
Section: Characterizationsupporting
confidence: 89%
“…This result was consistent with previous reports on oxygen‐functionalized carbon materials in Li cells. [ 53,54 ] Thus, the CCNs exhibited a substantially higher specific capacity of ≈420 mAh g −1 compared to nonfunctionalized CNs (≈197 mAh g −1 ) with a double‐layer capacitance‐based Li storage mechanism. Additionally, to better understand the electrolyte‐derived surface layer, the differential capacity vs. potential profiles of the electrodes were plotted from the 5 th GCD cycle at a current density of 0.1 A g −1 (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%